Fatigue analyses and life predictions of laser-welded lap-shear specimens made of low carbon and high strength low alloy steels. (November 2020) - Su, Zheng-Ming; Lin, Pai-Chen; Lai, Wei-Jen; Pan, Jwo; Cheng, Guan-Ju; Yen, Hung-Wei
Graphical abstract: Highlights: Fatigue analyses for LWed LS specimens made of LC and HSLA steels were conducted. Failure modes & fracture mechanisms of LWs in LCF & HCF were studied by OM & EBSD. FE models of LWs in LCF & HCF were developed to obtain global and local SIFs. Fatigue models made of local SIFs and Paris law were used for life predictions. Predicted fatigue lives show well agreement with experimental results. Abstract: This paper first presented fatigue analyses of dissimilar laser welds (LWs). Laser welded (LWed) lap-shear (LS) specimens made of low carbon (LC) and high strength low alloy (HSLA) steel sheets were used in quasi-static and fatigue tests. Failure loads and fatigue data of LWed LS specimens were obtained. The LWs before and after failure were examined by optical and scanning electron microscopes. Three failure modes and corresponding failure mechanisms were obtained in quasi-static, high-cycle and low cycle conditions. The quasi-static failure mode was controlled by necking failure in base metal of LC steel. The low-cycle fatigue failure mode was controlled by upper sheet separation in heat affected zone (HAZ) of LC steel, while the high-cycle fatigue failure mode was controlled by lower sheet separation in HAZ of HSLA steel. Finite element models of LWs with original cracks and finite kinked cracks in LS specimens were developed to obtain the corresponding global and local stress intensity factors (SIFs), respectively. Finally, the fatigue lives predicted by the fatigue model based on the local SIF solutions and Paris law agreed well with the experimental results.